PERILAKU SAMBUNGAN BALOK I DAN KOLOM TABUNG BAJA AKIBAT BEBAN SIKLIK - Hery Dualembang; Muslikh Muslikh; Andreas Triwiyono (Jurnal Teknik Sipil dan Teknologi Konstruksi, 2021)
Using Concrete-Filled Steel Tube (CSFT) as a column component provides many advantages over steel columns and reinforced concrete columns. Steel tube serve as reinforcement as well as formwork for concrete filler material. Besides, restrain effect of steel tube prevent crack in the concrete. The concrete-filler on steel tube prevent local buckling and increases the strength and stiffness of the column. The lack of experience and complexity of the beam-column connection system becomes an obstacle to use the CFST as a column. In addition, strength and stiffness of the connection system on CFST should be sufficient to endure the earthquake loads. This research purpose to find alternate connection of CFST column beams and also to know hysterestis behavior, strength, stiffness and pattern of connection collapse due to cyclic loading. There are two specimens in this research, continuous joint of beam-column steel tube with concrete filler (BKM-T) and continuous joint of beam-column steel tube without concrete filler (BKM-K).  BKM-K as a comparator to show an increasing strength and stiffness due to the concrete core. Load cycle of specimens refer to ACI 374.1-05. The test results showed the average maximum load (Ppeak) of 32.59 kN on BKM-K increased to 34.08 kN on BKM-T. Elastic stiffness (Ke) at BKM-K of 0.78 kN/mm increased to 1.08 kN/mm on BKM-T. BKM-T also has a larger hysteretic loop than BKM-K. In addition, BKM-K and BKM-T adequate the strong column weak beam criteria with partial ductility.